(untitled) (Bangladesh Journal of Neuroscience, 2016)
Background: Stroke is a major cause of physical disability in the elderly and the second most common cause of dementia. The prevalence of Alhzeimer’s dementia is increasing in western societies. But vascular dementia (VaD) is increasing in developing countries like Bangladesh and in Japan, because of the decline in mortality after stroke and aging of population. Conflicting data shows that hyperlipidaemia, a modifiable risk factor for ischemic stroke is associated with a higher risk of vascular dementia. Objective: The objective of this study was to evaluate association of hyperlipidaemia with vascular dementia. Method: It was a cross-sectional descriptive study conducted in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from August 2014 to November, 2015. All stroke patients above 18 years of age and both sexes, attending the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka presenting at least 3 months after stroke were the study population. Patients attending to the above mentioned hospital and after meeting the inclusion and exclusion criteria a purposive sampling technique were applied for selecting cases. Total 73 cases were evaluated. These patients were examined by MMSE for evidence of dementia. Severity and risk factors of vascular dementia were assessed. Serum fasting lipid profile was estimated in all cases and evaluated their association with VaD. Results: In this study it was observed that most of the stroke patients and VaD patients were in the age group of 5th and 6th decade. Among stroke patients it was 17(23.3%) and 31(42.5%) and among VaD patients it was 10(25.6%) and 18 (46.6%). Male outnumbered female (in stroke male-63%, Female-37%; in VaD male-59%, Female 41%). In this study out of 73 patients 40(54.8%) were smoker, 67(91.8%) had hyperlipidemia, 54(74%) had hypertension, 35(47.9%) had diabetes mellitus, 15 (20.5%) had IHD, 64(87.7%) had ischemic stroke, 9(12.3%) had hemorrhagic stroke, 25(34.25%) had recurrent stroke. Most of the patients were house-wife 16((21.9%) and read upto primary level 22 (30%). Out of 73 stroke patients 39(53.4%) had VaD. Of them 12(30.8%) had mild, 16(41%) had moderate and 11(28.2%) had severe dementia. Again out of 39 VaD patients 38(97.4%) had history of ischemic stroke and 1(2.6%) had history of hemorrhagic stroke who was moderately demented. Among VaD and non-vascular dementia patients the mean S. total cholesterol, S. triglyceride, S. LDL-C and S.HDL-C were 185.35±44.07, 149.82±57.05, 133.58±44.53, 31.07±11.16 (mg/dl) and 178.70±48.40, 151.35±76.12, 116.48±42.39, 33.61±11.82 (mg/dl) respectively. Conclusion-: In this study there is a non-significant positive association with high S. total cholesterol, high S. LDL-C, Low S. HDL-C but not with S. triglyceride. So, we can conclude that hyperlipidemia has weak association with VaD. Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 1-11